Penelitian Kerusakan Pada Sebuah Pipa Ketel Uap - Adnyana, D.N. (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Failure Investigation on Ruptured Boiler Tube, This paper presents a failureinvestigation on a ruptured steam boiler tube. This boilertubewas madeoflow carbonsteel, having 76.1mm outside diameter and 5 mmthickness. Theboiler tube was installed in horizontal position on thefrontrear walls ofa steam boiler that was operated at steam pressure and temperature of60 bar and 275